The Effect Of Acupuncture Therapy With Turmeric Herbal Combination On Stomach Pain In Students Of The Ministry Of Health Poltekkes In Surakarta - Zahro, Astrida Septi Berliana; Prasetya, Hanung; Wardoyo, Suwaji Handaru (Indonesian Journal of Acupuncture, 2025)
Gastric pain is one of the signs of gastritis in the form of digestive disorders due to an inflammatory process of the gastric mucosa and submucosa which is acute, chronic diffuse, or local. The purpose of this study was to determine the effect of acupuncture therapy with a combination of turmeric herbs on gastric pain in students of the Ministry of Health Polytechnic of Surakarta. This study used a Quasi-Experimental Design with a pretest and posttest design. This study was conducted in February-March 2024 at the Ministry of Health Polytechnic of Surakarta. The sample was students of the Ministry of Health Polytechnic of Surakarta who experienced gastric pain and met the inclusion and exclusion criteria. The sample was divided into two groups, each consisting of 15 children. Acupuncture therapy using CV 12, PC 6, ST 40, and SP 3 points. Combination using turmeric herbs. Data were analyzed using the Wilcoxon test. The test results showed a significance value of <0.001 (p <0.050). This study concludes that acupuncture therapy with a combination of turmeric herbs has an effect on gastric pain in students of the Ministry of Health Polytechnic of Surakarta.